Online Shopping Consumptive Behavior (Content Analysis of Comments on Twitter Account @RacunBelanja Period 1-31 December 2022) - Selvi Pusparini; Rr. Dinar Soelistyowati (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to reveal the types of consumptive behavior and describe the forms of cognitive, affective and behavioral effects that appear on followers of the @RacunBelanja account in the coments column of the @RacunBelanja Twitter account in December 2022. This research uses a qualitative method with a content analysis type of research. The data collection technique in this study was by means of documentation and observation on the Twitter account @RacunBelanja. The results of the study show that (1) There are four types of consumptive behavior that occur in the comments column of the Twitter account @RacunBelanja, namely buying products because of the lure of gifts, buying products based on price considerations (not on the basis of benefits or uses), buying products only just maintaining a status symbol and using a product because of conformity to the model that advertises, (2) Based on the results of the study it was found that in the comments column of the Twitter account @RacunBelanja in December 2022 there were cognitive effects, affective effects and behavioral effects